Targeting TGF-beta in human keratinocytes and its potential role in wound healing - Philipp, Katrin; Riedel, Frank; Sauerbier, Michael; Hörmann, Karl; Germann, Günter (International journal of molecular medicine, 2004)
The pathology of chronic dermal ulcers is characterized by excessive proteolytic activity which degrades extracellular matrix (required for cell migration) and growth factors and their receptors. The transforming growth factor-beta (TGF-beta) has been identified as an important component of wound healing. Recent developments in molecular therapy offer exciting prospects for the modulation of wound healing, specifically those targeting TGF-beta. We investigated expression of angiogenic bFGF and VEGF, and collagenases MMP-2 and MMP-9 in tissue samples from chronic dermal wounds by immunohistochemistry. The effect of TGF-beta targeting using antisense oligonucleotides on the expression of these factors was analysed by ELISA in human keratinocytes. Immunohistochemical investigation demonstrated a decreased expression of bFGF and VEGF protein, and an increased expression of MMP-2 and MMP-9 in tissue samples from chronic dermal wounds compared to normal human skin. Antisense TGF-beta oligonucleotide treatment down-regulated collagenase secretion activity and up-regulated VEGF secretion in vitro. Therefore, TGF-beta antisense oligonucleotide technology may be a potential therapeutic option for the inhibition of proteolytic tissue destruction, and stimulation of angiogenesis in chronic wounds. Improving basic knowledge and pharmaceutical intervention in this area ultimately may help clinicians to identify and proactively intervene in an effort to prevent normal wounds from becoming chronic.
Gesehen am 01.04.2022